Removal of Phenol in Batch Culture by Pseudomonas putida AP11, AP9, AP6 and AP7 Isolated from the Aromatic Hydrocarbon Contaminated Soils - Khan, M. A. I.; Fakhruddin, A. N. M.; Jame, S. A.; Sultana, M.S.; Alam, M. K. (Journal of Scientific Research, 2011)
Phenol widely used in industries, are of growing concern owing to their toxicity and wide distribution in industrial wastes. The aims of the study were to characterize some of the locally isolated bacteria and to develop suitable methods for the degradation of phenol using them. Locally isolated AP11, AP9, AP6 and AP7 were identified as Pseudomonas putida using the classical methods. Pseudomonas putida AP11 and AP9 were able to remove 600 ppm phenol completely, but Pseudomonas putida AP6 and AP7 were able to remove 400 ppm phenol completely. The maximum degradation rates for freely suspended culture of Pseudomonas putida AP11, AP9, AP6, AP7 were 10.83, 10.42, 8.33, and 8.33 (ppm/h) respectively. The isolates AP11, AP9, AP6 and AP7 can be used to wastewater containing phenol in effluent treatment systems. Keywords: Aromatic hydrocarbon; Carbon source; Contaminated soil; Phenol; Pseudomonas. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.6339 J. Sci. Res. 3 (2), 367-374 (2011)